Co-hydrothermal gasification of microbial sludge and algae Kappaphycus alvarezii for bio-hydrogen production: Study on aqueous phase reforming. (5th May 2021) - Jayaraman, Ramesh Sai; Gopinath, Kannapan Panchamoorthy; Arun, Jayaseelan; Malolan, Rajagopal; Adithya, Srikanth; Ajay, Pattabhiraman Srinivaasan; Sivaramakrishnan, Ramachandran; Pugazhendhi, Arivalagan
Abstract: In this study, wastewater obtained from a sewage treatment plant was treated successively by using microbial consortium and macroalgae Kappaphycus alvarezii to generate microbial sludge and algal biomass. The production of green fuel was carried out via co-gasification of microbial sludge and macroalgae Kappaphycus alvarezii for a duration of 60 min, feedstock to solvent ratio (5 to 20 g of feedstock in 200 mL), sludge to algae ratio (ranging from 1:1 to 3:1) and temperature (300–400 °C) respectively. Maximum bio-hydrogen yield was 36.1% and methane yield was 38.4% at a temperature of 360 °C at a feedstock to solvent ratio of 15:200 g/mL and sludge to algae ratio of 2:1 individually. The liquid by product of co-gasification process was later subjected to photocatalytic reforming, resulted in an enhanced hydrogen composition of 61.25%. Graphical abstract: Image 1 Highlights: Kappaphycus alvarezii and sludge was processed for bio-hydrogen production. Hydrothermal gasification resulted in syngas, biochar and liquid phase formation. Maximum bio-hydrogen yield was 36.1% for 2:1 (sludge: algae) at 360 °C. Methane yield was 38.4%, carbon dioxide was 19% for 2:1 ratio at 360 °C. Reforming of aqueous phase with 7.5 wt% catalyst showed 61.25% of bio-hydrogen.